A Randomized First‐in‐Human Study With UB‐312, a UBITh® α‐Synuclein Peptide Vaccine. Issue 7 (15th April 2022) - Yu, Hui Jing; Thijssen, Eva; van Brummelen, Emilie; van der Plas, Johan L.; Radanovic, Igor; Moerland, Matthijs; Hsieh, Eric; Groeneveld, Geert Jan; Dodart, Jean‐Cosme
Abstract: Background: α‐Synuclein (αSyn) is believed to play a central role in Parkinson's disease (PD) neuropathology and is considered a target for disease modification. UB‐312 is a synthetic αSyn peptide conjugated to a T helper peptide and is expected to induce antibodies specifically against oligomeric and fibrillar αSyn, making UB‐312 a potential immunotherapeutic for synucleopathies. Objective: To investigate the safety, tolerability, and immunogenicity of UB‐312 vaccination in healthy participants and to determine a safe and immunologically optimal dose for the first‐in‐patient study. Methods: Fifty eligible healthy participants were enrolled in a 44‐week, randomized, placebo‐controlled, double‐blind study. Participants in seven cohorts were randomized to three intramuscular UB‐312 or placebo injections at weeks 1, 5, and 13 (doses ranging between 40 and 2000 μg). Safety and tolerability were assessed by adverse events, clinical laboratory, vital signs, electrocardiograms, and neurological and physical examinations. Immunogenicity was assessed by measuring serum and cerebrospinal fluid (CSF) anti‐αSyn antibody concentrations. Results: Twenty‐three participants received all three vaccinations of UB‐312. Most adverse events were mild, transient, and self‐resolving. Common treatment‐emergent adverse events included headache, nasopharyngitis, vaccination‐site pain, lumbar puncture‐site pain, and fatigue. UB‐312 induced dose‐ and time‐dependent antibody production. Antibodies were detectable in serum and CSF of all participants receiving the 300/300/300 μg UB‐312 dose regimen. The average CSF/serum ratio was 0.2%. Conclusions: UB‐312 was generally safe, well tolerated, and induced anti‐αSyn antibodies in serum and CSF of healthy participants. The 100 and 300 μg doses are selected for further evaluation in participants with PD. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society